Assessing oxygen depletion in the Northeastern Pacific Ocean during the last deglaciation using I/Ca ratios from multiple benthic foraminiferal species. (3rd August 2017) - Taylor, M. A.; Hendy, I. L.; Chappaz, A.
Abstract: Paleo‐redox proxies are crucial for reconstructing past bottom water oxygen concentration changes brought about by ocean circulation and marine productivity shifts in response to climate forcing. Carbonate I/Ca ratios of multiple benthic foraminifera species from Ocean Drilling Program Hole 1017E—a core drilled within the Californian oxygen minimum zone (OMZ), on the continental slope—are employed to reexamine the transition from the well‐oxygenated last glacial into poorly oxygenated modern conditions. The redox and export productivity history of this site is constrained by numerous proxies used to assess sensitivity of I/Ca ratios of benthic foraminifera to changes in bottom and pore water O2 concentrations. Reconstructed iodate (IO3 − ) availability is from the I/Ca ratio of epifaunal ( Cibicidoides sp.), shallow infaunal ( Uvigerina peregrina ), and deep infaunal ( Bolivina spissa ) foraminifera. The reconstructed IO3 − availability profile is used to determine the contribution of bottom water O2 relative to oxidant demand on pore water O2 concentrations. These results suggest that high export productivity on the California Margin drove low pore water O2 concentrations during the Bølling. In contrast, low bottom water O2 concentrations at 950 m water depth only contributed to reduced sediments during the Allerød. Increased contribution of modified North Pacific Intermediate Water to the California Current System ventilated the California OMZ during the late glacial and the Younger Dryas such that water overlying the site was oxygenated. These results highlight the promising potential of this new proxy for understanding the relative influence of bottom water O2 concentration and pore water oxidant demand on OMZs. Plain Language Summary: Iodine is a highly redox‐sensitive element, is well mixed in the ocean, and is one of the first elements to respond to changes in ocean redox. In an oxic water column it is found as IO3 −, and with decreasing dissolved O2 concentration it is reduced to I − . In foraminiferal calcite, iodate is thought to substitute for carbonate ions proportionate to the IO3 − concentration of the water column, with the potential to be a quantitative proxy for detecting changes in oxygenation of bottom waters. However, core top studies indicate significant interspecies variability of I/Ca in response to O2 . Here we measured the I/Ca ratios of multiple benthic foraminiferal species from Ocean Drilling Program‐1017E, a high‐resolution core on the California margin of the Northeast Pacific Ocean, to reconstruct bottom and pore water iodate availability to reexamine the oxygenation history of the California oxygen minimum zone to investigate the potential of this proxy for reconstructing the relative influence of bottom and pore water oxidant demand in response to millennial‐scale climate changes compared with previously published trace metal redox proxies. Key Points: Three benthic foraminifera species show expected I/Ca ratios in Northeast Pacific core record relative to their depth habitat Foraminiferal I/Ca‐based O2 reconstructions are supported by multiple proxies in the same sediment samples Oxidant demand was greatest during the Bølling; pore and bottom waters were most oxygenated during the Younger Dryas and last glacial